Aptamer Applications in Forensic Science: Cocaine Detection and Latent Fingerprint Visualization Cases - Çağlayan, Mustafa Oğuzhan (The Bulletin of Legal Medicine, 2018)
Aptamers, also known as artificial antibodies, are capture elements that are attached to target molecules of different sizes with high affinity, and selectivity. They are successfully used in many different sensor applications over the last 30 years. Aptamers have unique advantages such as being able to be produced in a laboratory environment in contrast to antibodies produced via immunoactivity, easy to amplify and purify and to be produced in an infinite configuration. In addition to the military, environmental, food safety and medical applications, the use of aptamers in forensic sciences is inevitable. In this article, examples of aptamers and their applications in forensic sciences are given. Due to a large number of applications in the literature, latent fingerprint visualization and cocaine detection cases are given as examples of aptamer applications in forensic science.
Keywords: Aptamers; forensic science applications; biosensors; cocaine detection; latent fingerprint